A mixed-methods study to explore opinions of research translation held by researchers working in a Centre of Research Excellence in Australia. Issue 9 (10th September 2018) - Lynch, Elizabeth A; Ramanathan, Shanthi A; Middleton, Sandy; Bernhardt, Julie; Nilsson, Michael; Cadilhac, Dominique A
Abstract : Objective: There is a growing need for researchers to demonstrate impact, which is reliant on successful research translation. The Australian National Health and Medical Research Council funded a Centre of Research Excellence in Stroke Rehabilitation and Brain Recovery (CRE-Stroke) to enhance collaborations between researchers conducting different types of stroke rehabilitation research. The purpose of this study was to explore opinions about research translation held by CRE-Stroke researchers conducting preclinical and clinical research, in terms of scope, importance, responsibility and perceived skills and knowledge. Design: Mixed-methods study, comprising a paper-based survey and semistructured interviews. Interview data were inductively coded and thematically analysed. Survey and interview data were compared and synthesised. Participants: 55 (7 preclinical, 48 clinical) researchers attending a CRE-Stroke research forum completed a paper-based survey. Semistructured interviews with 22 CRE-Stroke (5 preclinical, 17 clinical) researchers were conducted. Results: Research translation was described as translating to other research and translating to clinical practice and policy. Most researchers (n=54, 98%) reported that research translation was important, particularly in terms of generating research impact, but the most common sign of project completion reported by researchers (n=7, 100% preclinical; n=37, 77% clinical) was publication. Most researchers (preclinical n=4, 57%; clinical n=37, 77%) reported having responsibility for translating research, but less than half reported having the necessary skills (n=1, 14% preclinical; n=17, 35% clinical) and knowledge (n=3, 43% preclinical; n=19, 40% clinical). Differing opinions about who should be responsible for translating findings to clinical practice were expressed. Conclusions: Stroke rehabilitation researchers appear confident to translate their research via the traditional mechanism of publications. To optimise impact, clarity is needed regarding who is best placed to translate research findings to clinical practice and policy. Education and skills development to apply broader translation processes are needed to maximise the use of research at all stages.